2021
DOI: 10.7324/japs.2021.110910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various stabilizers on the stability of lansoprazole nanosuspension prepared using high shear homogenization: Preliminary investigation

Abstract: The purpose of the current research work was to prepare a nanosuspension of the model drug lansoprazole (LSP) and investigate the effect of various stabilizers on the stability of the nanosuspension prepared using the high shear homogenization technique. In this study, polymeric stabilizers like polyvinylpyrrolidone K-30, polyvinylpyrrolidone K-90, polyvinyl alcohol, sodium alginate, and hydroxypropyl methylcellulose E15 and surfactants like sodium lauryl sulfate and Tween 80 were explored. The prepared nanosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore, the particle size distribution in the formulation was evaluated as PI, which gave a degree of PSD. The PI is an important evaluation parameter that controls the physical stability of nanosuspensions and should be kept as low as possible to achieve the long-term stability of a nanosuspension (Ubgade et al 2021). The present study indicated that the PIs of the produced ketoprofen nanosuspensions after three-month storage at room temperature were varied ranging from 0.374 ± 0.003 to 0.504 ± 0.035 depending on formulation compositions as shown in Table 4.…”
Section: Particle Size Pi and Zeta Potentialmentioning
confidence: 99%
“…Furthermore, the particle size distribution in the formulation was evaluated as PI, which gave a degree of PSD. The PI is an important evaluation parameter that controls the physical stability of nanosuspensions and should be kept as low as possible to achieve the long-term stability of a nanosuspension (Ubgade et al 2021). The present study indicated that the PIs of the produced ketoprofen nanosuspensions after three-month storage at room temperature were varied ranging from 0.374 ± 0.003 to 0.504 ± 0.035 depending on formulation compositions as shown in Table 4.…”
Section: Particle Size Pi and Zeta Potentialmentioning
confidence: 99%
“…In alignment with such an achievement, various studies showed that SD formulations were able to enhance drug bioavailability compared to pure LZP [9,10]. Moreover, Ubgade et al prepared a nanosuspension formulation of LZP and in vitro dissolution showed that the prepared formulation was able to enhance initial and total drug dissolution behavior compared to the pure drug [11].…”
Section: Introductionmentioning
confidence: 97%
“…For example, Zhang et al prepared an SD formul using fluid-bed coating technology where 90% of drug was dissolved at the e iment [8]. In alignment with such an achievement, various studies showed th lations were able to enhance drug bioavailability compared to pure LZP [9,10 Ubgade et al prepared a nanosuspension formulation of LZP and in vitro showed that the prepared formulation was able to enhance initial and total d tion behavior compared to the pure drug [11]. Self-nanoemulsifying drug delivery systems (SNEDDSs) incorporate tants, and co-surfactants to form nano-scale emulsion droplets upon mild a hancing the surface area for dissolution and absorption compared to the dru Recent research incorporated naturally derived oils with biological activities a to potentially augment the therapeutic activity of administered therapeut [13].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure nanosuspension stability, a minimum zeta potential of ± 30 mV is typically required(Ubgade et al 2021). The negative zeta potential in silver nanoparticles, likely due to bio-organic capping from plant extracts, enables electrostatic repulsion, preventing agglomeration and ensuring stability(Liaqat et al 2022).…”
mentioning
confidence: 99%